PENGARUH UKURAN DEWAN KOMISARIS DAN UKURAN DEWAN DIREKSI TERHARAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Thendean, Claudia Adelina; Meita, Iren (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
This study aims to determine the effect of Good Corporate Governance on Corporate Value with Intitusional Ownership as a moderating variable. In this study, Good Corporate Governance is measured by 2 variables, namely the size of the board of commissioners and the size of the boardof directors. The Company's value is measured by Earning Per Share. The sample of this research is 9 insurance companies listed on Indonesia Stock Exchange period 2011- 2015 period. The results of this study are the size of the board of commissioners and the size of the board ofdirectors does not affect the value of the company; The size of the board of commissioners and the size of the board of directors simultaneously has no effect on the value of the company; Institutional ownership may moderate the size of the board of commissioners to the value of thecompany; And institutional ownership can moderate the size of the board of directors against corporate value.